Editorial craft and francophone African literature: The case of Malick Fall. (September 2014) - Bush, Ruth
This article considers Senegalese novelist Malick Fall's 1967 novel La Plaie [The Wound] in the light of material from the archives of Parisian publishers Editions du Seuil. It explores to what extent and with what effect traces of editorial mediation revealed in publishers' archives can be written into the history of francophone African literature. Fall's long-neglected text is one of the earliest francophone African novels of post-independence disillusionment. Described by an early critic as the first African "existentialist" novel, its fragmented narrative draws on seams of poetic symbolism, burlesque comedy, and philosophical reflection to portray a vagrant protagonist. The complex structure and unstable narrative voice mark a departure from realist modes of African novels in the 1950s. Moreover it troubles any reductive account of a linear transition from realism to modernism. Yet Fall's work remains much less known than the celebrated stylistic innovation of Ahmadou Kourouma's Les Soleils des indépendances (1968) or Yambo Ouologuem's Le Devoir de violence (1968). Readers' reports at Le Seuil, a publisher with clear anti-colonial sympathies, show how editors sought to revise Fall's manuscript according to normative ideas of language, genre, and literary craft, tentatively pointing to the text's modernist leanings without fully articulating what such modernity might constitute or imply. While clearly not exclusive to African or postcolonial literature, such stylistic tempering (or tampering) arguably shaped the text's meditations on trauma, freedom, and alienation. This evidence leads to a revised, multivalent understanding of Fall's literary innovation.